Psychometric Properties of the Photograph Series of Daily Activities-Short Electronic Version (PHODA-SeV) in Patients With Chronic Low Back Pain - Oliveira, Crystian Bitencourt [UNESP]; Franco, Marcia Rodrigues; Demarchi, Samantha Janaina [UNESP]; Smeets, Rob Johannes E. M.; Huijnen, Ivan P. J.; Morelhao, Priscila Kalil [UNESP]; Hisamatsu, Thalysi Mayumi [UNESP]; Pinto, Rafael Zambelli (J O S P T, 2018)
BACKGROUND: The Photograph Series of Daily Activities-short electronic version (PHODA-SeV) assesses perceived harmfulness of daily activities in patients with low back pain (LBP). Although there is some evidence that the PHODA-SeV is a reliable and valid tool, its psychometric properties have not been fully investigated. OBJECTIVES: To investigate the test-retest reliability, measurement error, interpretability, construct validity, and internal and external responsiveness of the PHODA-SeV in patients with chronic LBP. METHODS: Ninety-one patients were included in the analysis for this prospective cohort study. For reliability purposes, the PHODA-SeV was administered twice, with a 1-week interval before beginning treatment. Pain, disability, and measures of pain-related fear (ie, PHODA-SeV, Fear-Avoidance Beliefs Questionnaire [FABQ], and Tampa Scale of Kinesiophobia [TSK]) were collected before and after the 8-week treatment period. RESULTS: The PHODA-SeV showed excellent reliability (intraclass correlation coefficient model 2,1 = 0.91), without evidence of ceiling and floor ef-fects. The construct validity analysis demonstrated fair correlations (r = 0.25-0.50) of the PHODA-SeV with the FABQ, but no correlation with the TSK (r<0.25). For internal responsiveness, the PHODA-SeV showed an effect size of 0.87 and a standardized response mean of 0.92, interpreted as a large effect (greater than 0.80). For external responsiveness, the correlations between the PHODA-SeV and changes in the TSK and FABQ were considered low, and the receiver operating characteristic curve analyses revealed an area under the curve lower than the proposed threshold of 0.70. CONCLUSION: The PHODA-SeV is a reliable tool that can detect changes over time in pain-related fear in patients with chronic LBP undergoing physical therapy treatment. This tool, however, failed to identify those patients who did or did not improve, according to other pain-related fear measures.
Keywords: chronic low back pain; pain-related fear; reliability; responsiveness; validity